Hubungan kejadian diare pada balita dengan sikap dan pengetahuan ibu tentang perilaku hidup bersih dan sehat (PHBS) - Elfida Elfida; Azwari Azwari; Eva Sulistiany (Jurnal Kesehatan Ibu dan Anak, 2014)
Diarrhea is a condition in which a sudden change in bowel movements than usual ,which ismore often the frequency and amount and consistency aswater .Thenegative impact ofdiarrheal disease ininfants areableto inhibit the growth of childrenwho ultimately can degrade the quality of life of children .Daire disease can be prevented if people can apply to live clean and healthy behaviors (PHBs ) . This study aims to determine the relationship of Genesis Diarrhea In Toddlers With knowledge and Attitudes AboutBehavioral Mrs. Clean and Healthy At Sungai Pauh subdistrict Langsa City in 2013, using descriptive correlation research design . Sampling was done by stratified random samplingmethod .The population in this study is that motherswith toddlers in the village of Sungai Pauh In 2012 , the sample size in this study were 53 respondents . The data was collected fromApril 1, s/d 12 April 2013 using the questions inthe formof sheet questionnaire.Data processing was performed usingSPSSwindow's15,while the analysis of the data presented in the formof univariate and bivariate tables .Of the 53 mothers, themajority ofmothers with children under five with diarrhea as many as 27 mothers ( 50.9 % ) . Of the 38 mothers who are knowledgeable about good hygiene practices, healthy totai of 19mothers (50.0%)had childienwith diarrhea , from 9mothers are knowledgeable enough by 7mothers (77.3%) had children with diarrhea.While themother of 6 less knowledgeable , asmany as 1mothers ( 16.7%) had children with diarrhea . Of the 42motherswho had positive attitudes about healthy living behaviors ,asmany as 22mothers (52.4%)had childrenwho had diarrhea Meanwhile the mother of 11 who have a negative attitude , as much as fivemothers ( 45.5%) had children who diarrhea .Based on the results of Chi Square statistic obtained results there is no relationship between knowledge (p- 0.066 > 7-0.05) ,attitude (p= 0.682 >? -0.05) , of good hygiene practices and healthy with the incidence of diarrhea in infants in the Village river Pauh subdistrict Langsa Kota.Dengan the research is expected to improve the quality of care at the health center Langsa city , especially nurses , should provide correct information regarding the procedure to avoid diarrheal diseases , so that mothers with toddlers can prevent and tackletheseat home.